Spherical aromaticity in I(h) symmetrical fullerenes: The 2(N+1)2 rule - Hirsch, Andreas; Chen, Zhongfang; Jiao, Haijun (Angewandte Chemie International Edition, 2000)
The maximal spherical aromaticity of an icosahedral fullerene such as C/ (see picture) can only be achieved with 2(N+1) π electrons. There is clear evidence for this rule from the magnetic behavior of the endohedral He complexes on the basis of He NMR chemical shifts and it is ascribed to the spherical charge distribution.